Clinical Value of Prostacyclin and its Analogs in the Management of Pulmonary Arterial Hypertension - Dandel, M.; Hetzer, R. (Current Vascular Pharmacology, 2003)
Pulmonary arterial hypertension (PAH) is associated with changes in vascular tone as well as vascular structure, with the relative contribution of each dependent upon the etiology of the increased vascular resistance. Prostacyclin treatment has markedly improved both the therapeutic options and the prognosis of PAH. The beneficial effect of prostacyclin in PAH is linked to the powerful vasodilating capacity and, even more importantly, to the inhibition of platelet aggregation, smooth muscle proliferation and antiinflammatory actions. Since prostacyclin has a very short plasma half-life, continuous intravenous administration via a portable infusion pump must be carried out. Because of the complexity of the delivery and the associated complications, intravenous prostacyclin (epoprostenol) therapy is restricted to patients with late NYHA Class III and Class IV and thus alternative modes of delivery in less advanced PAH are desirable. Recent clinical studies with more stable prostacyclin analogs such as subcutaneously delivered treprostinil, orally active beraprost and aerosolized iloprost have demonstrated beneficial effects of each of these prostanoids, especially in NYHA Class II and III patients and, therefore, these agents should be considered first for prostanoid therapy in the early stages of PAH. Prostaglandins may be more effective in conjunction with endothelin receptor antagonists or phosphodiesterase inhibitors and an increasing number of studies are now addressing the combined efficiency and safety of these combinations.This update will focus on the current development status of PAH therapy with prostacyclin and its analogs. Special attention will be accorded to the selection of patients for prostanoid therapy, therapy monitoring and improvement of therapeutic efficacy by addition of other new therapeutic agents to prostaglandins. Survival benefits and special aspects of bridging-to-transplant therapy are also important aspects of the review.
Keywords: prostaglandins